2011
DOI: 10.1186/1471-2164-12-288
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and tissue-enriched small RNAs in the plant pathogenic fungus, Magnaporthe oryzae

Abstract: BackgroundEmerging knowledge of the impact of small RNAs as important cellular regulators has prompted an explosion of small transcriptome sequencing projects. Although significant progress has been made towards small RNA discovery and biogenesis in higher eukaryotes and other model organisms, knowledge in simple eukaryotes such as filamentous fungi remains limited.ResultsHere, we used 454 pyrosequencing to present a detailed analysis of the small RNA transcriptome (~ 15 - 40 nucleotides in length) from myceli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 60 publications
10
97
1
Order By: Relevance
“…Filamentous fungi, with one billion years of evolution, are an important group of multicellular eukaryotes (Hedges et al 2004). Small RNA pathway also had been proved in filamentous fungi in different researches (Nicolas et al 2010;Nunes et al 2011). Recently, Lee et al (2010) reported that miRNA-like small RNAs (milRNAs) also exist in the filamentous fungus Neurospora crassa.…”
Section: Introductionmentioning
confidence: 99%
“…Filamentous fungi, with one billion years of evolution, are an important group of multicellular eukaryotes (Hedges et al 2004). Small RNA pathway also had been proved in filamentous fungi in different researches (Nicolas et al 2010;Nunes et al 2011). Recently, Lee et al (2010) reported that miRNA-like small RNAs (milRNAs) also exist in the filamentous fungus Neurospora crassa.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of sRNAs from many species of fungi has led to the discovery of many classes of them, e.g., siRNAs in Schizosaccharomyces pombe, Saccharomyces castellii, Candida albicans, Cryptococcus neoformans, and Magnaporthe oryzae; qiRNAs (QDE-2-interacting RNAs) in N. crassa; priRNAs (primal small RNAs) in S. pombe; ex-siRNAs (exonic-siRNAs) in Mucor circinelloides and T. atroviride; disiRNAs (Dicer-independent small interfering RNAs) in N. crassa, and milRNAs (miRNAslike small RNAs) in N. crassa, Sclerotinia sclerotiorum, Metharizium anisopliae, C. neoformans, and T. reesei. The functional role of some of these classes of sRNAs has been proven, but for many others it still remains to be shown (50,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67). For T. atroviride, however, a functional characterization of the components of the RNAi machinery is already available.…”
Section: Genome Integrity Genome Defense Mechanismsmentioning
confidence: 99%
“…Based on their RNA precursors and biogenesis mechanisms, these small RNAs can be divided into various types in fungi, including QDE-2-interacting small RNAs (qiRNAs), microRNA-like RNAs (milRNAs), Dicer-independent small interfering RNAs (disiRNAs), small interfering RNAs (siRNAs), long terminal repeat retrotransposon-siRNAs (LTR-siRNAs) and tRNA-derived RNA fragments (tRFs) (Jöchl et al 2008; Lee et al 2009; Nicolas et al 2010; Nunes et al 2011). The maturation of small RNAs in the RNA-silencing pathway is dependent on the RNase III ribonuclease Dicer, RNA-dependent RNA polymerases (RdRps) and Argonaute proteins (Lee et al 2010).…”
Section: Introductionmentioning
confidence: 99%